Early 20th century historical buildings with closed yard spaces in the city of Tambov - Zhorkina Darya G. (Архитектон, 2024)
The emergence and evolution of closed courtyards, a new element of the urban planning structure in the late 19th-early 20th century, is described based on a study of three historical buildings with enclosed courtyard spaces located in the city of Tambov.